Pneumatic tools for vitreoretinal surgery - Romano MR (Dove Medical Press, 2012)
Mario R Romano, Jose Luis Vallejo-Garcia, Alessandro Randazzo, Paolo VinciguerraIstituto Clinico Humanitas, Via Manzoni 56, 20089 Rozzano, Milan, ItalyAbstract: One of the difficulties of microsurgery is learning how to control physiological tremors. The pneumatic tool eliminates the physiological tremor, but no tactile feedback is provided. The manual tremor when closing the forceps is completely eliminated and the exact target can be more easily grabbed. Forceps closure pressure can rise up to 50 psi, whereas the scissors can be used in two modes: multicut and proportional. When performing bimanual surgery the pedal range is divided into two steps: in the first step, the forceps are controlled, and in the second step, the forceps remain closed. At the same time the scissors start to work in the preselected mode. No adverse events occurred and no iatrogenic retinal breaks were produced. Precision and control sensation were a grateful surprise.Keywords: pneumatic forceps, pneumatic scissors, physiological tremor